Experimental and theoretical investigations on debromination pathways of polybrominated biphenyls (PBBs) under ultraviolet light. (December 2018) - Wang, Rui; Tang, Ting; Feng, Siyuan; Chen, Xingwei; Dang, Dai; Huang, Kaibo; Tao, Xueqin; Yin, Hua; Dang, Zhi; Lu, Guining
Abstract: Polybrominated biphenyls (PBBs) are brominated flame retardants that are widely used in textiles and electronic products. Recently, many researches have been devoted to determining their concentrations in food and in the environment. Yet, their degradation behavior has been less investigated and is not well understood. Here, we have investigated the debromination pathways of PBBs by (UV) light in the case of 2, 4, 5-tribrominated biphenyl (PBB-29). Our investigation indicates that para- bromine substituent on PBB-29 was preferentially removed. By means of density functional theory (DFT), we found that the energies of the debromination products, the CBr bond length in the excited state (S1 ), the Mulliken charge of bromine in S1, and the lowest unoccupied molecular orbital (LUMO) in S1 correlated well with the debromination pathways of PBBs. Further, LUMO-based prediction of PBB debromination pathways in S1 suggests that the bromine substituent on all brominated positions (i.e. ortho-, meta- and para- ) can be preferentially removed, as the debromination sequence is not based on the brominated position but on the specific brominated arrangement pattern. In addition, reductive debromination preferentially occurs on the benzene ring that has the highest number of bromine substituents. This study provided useful descriptors to predict the debromination pathways of PBBs, and the theoretical result greatly improve our understanding of photolytic debromination of PBBs. Highlights: PBB-29 preferentially debrominate para- bromine substituent under UV light. Four quantum descriptors of PBBs were correlated well with their pathways. Debromination pathways of PBBs are based on the brominated arrangement pattern. Debromination prefers to occur on the benzene ring with more bromine substituents.